Integrating model and smartphone technologies for cold-water thermoregulation assessment - Yermakova, Irena; Volkov, Oleksandr; Nikolaienko, Anastasiia; Hrytsaiuk, Oleh; Tadeieva, Julia (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates human thermal and physiological responses during water immersion. The task addressed relates to the current gap between sophisticated, expert-driven mathematical models of thermoregulation and the practical demand for accessible tools to assess thermal risks in open water. To bridge the gap, this paper proposes a method based on the integration of a multicompartmental mathematical model of human thermoregulation with a mobile application. The results of the study confirm the method's effectiveness in predicting human physiological responses during water immersion. Model validation against experimental data demonstrated strong concordance, particularly in reproducing core temperature dynamics under cold-water exposure (Theil index ≈ 0; t(9) = 2.16, p > 0.05). Modeling results indicate that moderate activity (300 W) in water at a temperature of 10°C leads to a decrease in internal temperature, whereas higher activity levels (600 W) are sufficient to maintain normal body temperature. Wetsuits play a critical role in preserving human temperature regime during cold-water immersion; without a wetsuit, passive immersion at 17°C results in hypothermia within 60 minutes (Tcore < 36°C). Conversely, during high-intensity exercise (1100 W), wetsuits may increase thermal strain, with body temperature rising to 39.2°C over 60 minutes, while in the absence of protective clothing – Tcore = 38.1°C. The findings provide quantitative insights into the influence of water, immersion level, activity, and wetsuit on human thermal responses. The app that was developed could predict safety guidelines for aquatic sports and recreational activities.